2005
DOI: 10.1086/497382
|View full text |Cite
|
Sign up to set email alerts
|

Interaction betweenBurkholderia pseudomalleiand the Host Immune Response: Sleeping with the Enemy?

Abstract: Melioidosis is an infectious disease endemic in tropical and subtropical areas but is most often described in Southeast Asia and northern Australia. It has increasingly gained attention in the Western Hemisphere because of its potential use as a biological weapon. Progress in our understanding of the virulence mechanisms of Burkholderia pseudomallei, the causative agent, has provided clues to the pathogenesis of the disease. The bacterium can remain latent in the body for long periods of time and also possesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 53 publications
2
50
0
Order By: Relevance
“…In addition to these clinical similarities, we have described significant similarities between the pathological changes associated with tuberculosis and those seen in a chronic melioidosis animal model that we have developed, which include multiple-granuloma formation (36). Besides the similar lung pathology, both B. pseudomallei and M. tuberculosis infections can enter into a dormant phase, where there are no signs of infection (8,24).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In addition to these clinical similarities, we have described significant similarities between the pathological changes associated with tuberculosis and those seen in a chronic melioidosis animal model that we have developed, which include multiple-granuloma formation (36). Besides the similar lung pathology, both B. pseudomallei and M. tuberculosis infections can enter into a dormant phase, where there are no signs of infection (8,24).…”
mentioning
confidence: 93%
“…Little is known about latent B. pseudomallei infections, but the striking similarity to M. tuberculosis infections has led to speculations that these organisms use similar pathways to produce latency (8). For example, both M. tuberculosis and B. pseudomallei are able to survive for long periods of time in a dormant or nondividing state in vitro (20,38), and it has been hypothesized that these organisms may remain in a similar state during latent pulmonary infections.…”
mentioning
confidence: 99%
“…1 When acquired by humans and animals, B. pseudomallei can cause melioidosis, a life-threatening disease that, to this day, still presents a danger to most parts of the tropics. 2 Decades of research on B. pseudomallei has only revealed how versatile this pathogen is, for example, it can (1) infect a multitude of organisms and invade a wide range of cell types, 3,4 (2) result in a broad spectrum of clinical manifestations, 5 (3) resist many clinical antimicrobials 6 and (4) survive extremely harsh environmental conditions. 7 Yet, the molecular mechanisms by which B. pseudomallei evades or modulates host immune responses remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus infection (64). Gan (65) suggested that the development of acute melioidosis is due not to a lack but rather an excess of inflammation and a failure of regulatory mechanisms. We observed increased levels of antiinflammatory cytokines at 48 h p.i.…”
Section: Discussionmentioning
confidence: 99%